Knowledge and practice of personal hygiene among secondary school students of grade nine and ten (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Personal hygiene deficiency have been found to be a serious public health problem and people often affected are school children. These have been attributed to inadequate knowledge of personal hygiene and its practices. This study was designed to explore the existing knowledge and practices of personal hygiene among the students studying at secondary level schools in Bhaktapur district, Nepal.Methods: This study was a cross- sectional study to investigate personal hygiene knowledge and practices of secondary level, grades nine and ten school children, Bhaktapur district, Kathmandu valley, Nepal. Pre-tested, self- administered questionnaire were used. Data were collated and analyzed descriptively.Results: The result showed that the secondary school students who participated in the study were evenly distributed by gender (50.4% males and 49.6% females),most of the respondents (78.8%) were in the 15-16 year age bracket. Majority of the respondents (88.5%) had good knowledge level on personal hygiene. Female students were found having more knowledge level than male students. Conversely, majority of them were noted with moderate to poor level of hygiene practices.Conclusions: Secondary school students of Bhaktapur have good knowledge on personal hygiene while lot more improvement is required in terms of practices. Integrated approach by parents, school and social media to enhance hygiene practices could be useful.